2015
DOI: 10.1007/s10753-015-0243-9
|View full text |Cite
|
Sign up to set email alerts
|

Veratric Acid Inhibits LPS-Induced IL-6 and IL-8 Production in Human Gingival Fibroblasts

Abstract: Veratric acid, one of the major benzoic acid isolated from vegetables and fruits, has been reported to have anti-inflammatory activity. The purpose of this study was to investigate the anti-inflammatory effects of veratric acid on lipopolysaccharide (LPS)-induced inflammatory response in human gingival fibroblasts (HGFs). HGFs were pretreated with veratric acid 1 h before LPS stimulation. The productions of IL-6 and IL-8 were detected by ELISA. The expression of iNOS, COX-2, PI3K, AKT, and NF-κB were detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 30 publications
0
18
1
Order By: Relevance
“…OL-4 is a kind of anti-inflammatory cytokines and an important immunological regulators, which has immunomodulatory effects on T and B lymphocytes and macrophages, and play an important role in the proliferation, differentiation and functional regulation of T cells (Li et al, 2010). OL-8 is mainly produced by monocytes, endothelial cells and macrophages, which is an important proinflammatory cytokine and could attract neutrophils, macrophages and other inflammatory cells to migrate to inflammatory foci, activating the inflammatory response (Wang et al, 2016). Therefore, the present study would explore the anti-inflammatory mechanism of GED on ACD concerning these inflammatory cytokines stated above.…”
Section: Effect Of Geo On Gene Expression Of Inflammatory Cytokines Omentioning
confidence: 98%
“…OL-4 is a kind of anti-inflammatory cytokines and an important immunological regulators, which has immunomodulatory effects on T and B lymphocytes and macrophages, and play an important role in the proliferation, differentiation and functional regulation of T cells (Li et al, 2010). OL-8 is mainly produced by monocytes, endothelial cells and macrophages, which is an important proinflammatory cytokine and could attract neutrophils, macrophages and other inflammatory cells to migrate to inflammatory foci, activating the inflammatory response (Wang et al, 2016). Therefore, the present study would explore the anti-inflammatory mechanism of GED on ACD concerning these inflammatory cytokines stated above.…”
Section: Effect Of Geo On Gene Expression Of Inflammatory Cytokines Omentioning
confidence: 98%
“…Most noticeably, IL-8 and IL-6 levels by ELISA assay (reported in the same way as described above) constitute Figure 3 in these two manuscripts. In one case [8], Figure 2 includes IL-8 and IL-6 supernatant levels measured by ELISA within a multi-panel figure that also comprises iNOS and COX-2 levels by Western Blot (WB). This graph panel can also be found in the study by Li et al [32]; however, in that study it constitutes Figure 1, because the cell viability assay (CCK-8 in this study) is only described in the Results section, but data are not shown.…”
Section: Figurementioning
confidence: 99%
“…The third figure of the template is usually composed by a multi-panel figure that comprises photos of WB membranes labelled with anti phospho-p65, phospho-IkB, with α-Actin as reference and two bar charts, on the right side of the photos, obtained by the quantitation of the intensities of the WB signals ( Figure 3) [8,10,12,15,19,20]. The WB lanes are constituted by the Control group, the LPS-only group and LPS and three increasing concentrations of the test compound.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Tumor necrosis factor (TNF)α and interleukin (IL)-1β, as two of the important proinflammatory mediators, were significantly upregulated in the process of periodontitis, which are actively involved in jeopardizing periodontal tissues by affecting the activities of leukocytes, osteoclasts and collagenolytic enzyme matrix metalloproteinases (MMPs) to mediate alveolar bone resorption and collagen destruction. [13][14][15] Recent studies demonstrate that the host is predominantly responsible for tissue destruction in the periodontal inflammatory process, which leads to the clinical symptoms of periodontitis. 16,17 Host response can provide the potential for reducing tissue destruction by improving excessively elevated inflammatory process to enhance opportunities for periodontal stability and repair.…”
Section: Introductionmentioning
confidence: 99%